2020
DOI: 10.3390/molecules25163756
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical Synthesis and Evaluation of Novel Radioconjugates of Neurokinin 1 Receptor Antagonist Aprepitant Dedicated for NK1R-Positive Tumors

Abstract: Aprepitant, a lipophilic and small molecular representative of neurokinin 1 receptor antagonists, is known for its anti-proliferative activity on numerous cancer cell lines that are sensitive to Substance P mitogen action. In the presented research, we developed two novel structural modifications of aprepitant to create aprepitant conjugates with different radionuclide chelators. All of them were radiolabeled with 68Ga and 177Lu radionuclides and evaluated in terms of their lipophilicity and stability in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…The opioid fragment extends towards the extracellular outlet of the receptor and the simulations suggest some mobility of this fragment, however an interaction between Tyr 1 amine and Glu193 is present for a great part of the collected trajectories. Notably, a polar interaction between Glu193 and small molecular ligand was also found in the experimental structure of aprepitant/NK1R complex [65] but SAR data suggest that it is not indispensable to high-affinity binding since the modification [73] or functionalization [74] of the interacting triazolinone ring results in relatively moderate affinity decreases. Moreover, E193A mutation has virtually no effect on aprepitant's affinity.…”
Section: Discussion Of the In Silico Resultsmentioning
confidence: 90%
“…The opioid fragment extends towards the extracellular outlet of the receptor and the simulations suggest some mobility of this fragment, however an interaction between Tyr 1 amine and Glu193 is present for a great part of the collected trajectories. Notably, a polar interaction between Glu193 and small molecular ligand was also found in the experimental structure of aprepitant/NK1R complex [65] but SAR data suggest that it is not indispensable to high-affinity binding since the modification [73] or functionalization [74] of the interacting triazolinone ring results in relatively moderate affinity decreases. Moreover, E193A mutation has virtually no effect on aprepitant's affinity.…”
Section: Discussion Of the In Silico Resultsmentioning
confidence: 90%
“…The SP stimulus is crucial for the survival of tumor cells, and the overexpression of the NK-1R in cancer cells provides an excellent tool for its therapeutic use. Thus, due to this overexpression, NK-1R ligands (e.g., 213 Bi-DOTA-[Thi 8 ,Met(O2) 11 ] substance P and radioconjugates of aprepitant) have been developed and used in targeted radionuclide tumor therapy with promising results for selective irradiation to kill cancer cells [6,7,146]. DOTA-SP showed a lower uptake by normal cells than by tumor cells, and this has been related to the higher number of NK-1Rs expressed in the latter cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antitumor action of aprepitant/fosaprepitant has been confirmed (both compounds decreased the volume of the tumor) in experimental mouse models (MG-63 human-osteosarcoma and HuH6 human-hepatoblastoma xenografts). Finally, several studies have been reported on the use of aprepitant (in combination with radiotherapy) in a patient suffering from lung cancer [5] or in nuclear medicine for the diagnostic/treatment of tumors expressing the NK-1R [6,7]. Both therapeutic strategies have shown promising results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one article on CIP labelled with Ga-68 in the literature [21], where the authors used either a macrocyclic DOTA (p-SCN-Bz-DOTA) or NOTA (p-SCN-Bz-NOTA) chelator, additionally attached to CIP via a propylamine (PA) linker. In our study, based on our own experience [22] and in order to avoid introducing into the radiopreparation molecule additional chemical fragments containing thiourea bonds [23], we used a DOTA-NHS chelator. The role of CIP in these radiopreparations is to act as a biologically active molecule (vector), which targets the radiopharmaceutical directly to the infected area with high specificity, allowing its precise visualisation by SPECT or PET.…”
Section: Introductionmentioning
confidence: 99%